Cultural Effects on the Diagnosis of Autism Spectrum Disorder Among Latinos. (December 2016) - Ratto, Allison B.; Reznick, J. Steven; Turner-Brown, Lauren
The role of culture in autism spectrum disorders (ASD) has been too often neglected in research. The present study evaluated the implications of cultural factors for ASD screening and diagnosis by examining the parenting perceptions and diagnostic experiences of Latina and White mothers of children with ASD. The children of Latina mothers were diagnosed significantly later and were significantly more likely to be diagnosed with autism than with another ASD. Latina mothers demonstrated significantly less knowledge of developmental milestones and of ASD. Latina mothers were also significantly more likely to report early concerns about temperament. The results of this study suggest that both socioeconomic and culturally based differences likely influence the early perception and diagnosis of ASD.